An outer measure on a commutative ring - Dudzik, D.; Skrzyński, M. (Algebra and Discrete Mathematics, 2016)
We show how to produce a reasonable outer measure on a commutative ring from a given measure on a family of prime ideals of this ring. We provide a few examples and prove several properties of such outer measures.